2016
DOI: 10.5194/cp-12-769-2016
|View full text |Cite
|
Sign up to set email alerts
|

The WAIS Divide deep ice core WD2014 chronology – Part 2: Annual-layer counting (0–31 ka BP)

Abstract: Abstract. We present the WD2014 chronology for the upper part (0–2850 m; 31.2 ka BP) of the West Antarctic Ice Sheet (WAIS) Divide (WD) ice core. The chronology is based on counting of annual layers observed in the chemical, dust and electrical conductivity records. These layers are caused by seasonal changes in the source, transport, and deposition of aerosols. The measurements were interpreted manually and with the aid of two automated methods. We validated the chronology by comparing to two high-accuracy, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
221
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 196 publications
(229 citation statements)
references
References 86 publications
7
221
0
1
Order By: Relevance
“…Fundamental differences exist, however, between sedimentation processes and aeolian deposition in these environments. Varying amounts of dust in ice attest to both hydro-and lithospheric changes on the continents and long distance transport (Palais and Legrand, 1985;Mahowald et al, 1999;Petit et al, 1999;Sigl et al, 2016). Ion loads in Byrd and WD_3 corroborate these reports, with OM quantity and quality assessments, alongside traditional climate indicators, proving suitable as palaeoecological markers.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Fundamental differences exist, however, between sedimentation processes and aeolian deposition in these environments. Varying amounts of dust in ice attest to both hydro-and lithospheric changes on the continents and long distance transport (Palais and Legrand, 1985;Mahowald et al, 1999;Petit et al, 1999;Sigl et al, 2016). Ion loads in Byrd and WD_3 corroborate these reports, with OM quantity and quality assessments, alongside traditional climate indicators, proving suitable as palaeoecological markers.…”
Section: Discussionsupporting
confidence: 67%
“…From their study on the vertical profile of microorganisms in ice, Zhang et al (2006) concluded that less dust and microbial species were deposited during warmer periods. The three-fold lower numbers of OTUs and lower dust concentrations in the WD_3 core (Sigl et al, 2016) follow this trend. It is important to note that although both cores were retrieved from West Antarctica (separated by ~161 km), aerosols over ice sheets may differ between locations (Rothlisberger et al, 2000).…”
Section: Discussionmentioning
confidence: 64%
“…S1 and S2) show that the glaciochemical anomaly consisted of nine pulses measured between 2,426.97 m and 2,420.04 m depth in the WD core, corresponding to a ∼192-y period from 17.748 ka to 17.556 ka (Fig. 2) on the WD2014 timescale (18). Evidence of this glaciochemical anomaly also has been traced throughout West Antarctica and parts of East Antarctica in ice cores (17) (Fig.…”
Section: Significancementioning
confidence: 96%
“…S1 and S2). WD snow accumulation was relatively high (>100 kg·m −2 ·y −1 ) during this period (18), so the regions of high acidity in the core were well separated from regions of low acidity. Second, consistent with modern observations in which some but not all volcanic eruptions are associated with ozone depletion (26), evaluation of the 100 highest acidity events (annual average concentration >3.0 μeq·L −1 ) in the 10 ka to 25 ka WD record shows that 30% were not associated with bromine depletion and that depletion was not proportional to acidity (SI Appendix, Fig.…”
Section: Evidence For Stratospheric Ozone Depletionmentioning
confidence: 96%
“…Measurements of δD of ice and δ 15 N of trapped N 2 were by laser spectroscopy and mass spectrometry, respectively (15, 47) (SI Ice-Isotopic Data and SI Nitrogen-Isotopic Data). The age-depth relation and annual layer thicknesses were determined by identifying and counting annual layers back to ∼31 ka and by cross-correlations of gas records prior to this time (16,47,53) N(t). Given simultaneous histories of accumulation rate (ḃ(t)) and Ts(t), we calculated firn density profiles using an empirical model (20), recast to use overburden load as a driving variable as in refs.…”
Section: Methodsmentioning
confidence: 99%